2018
DOI: 10.1016/j.comppsych.2018.08.011
|View full text |Cite
|
Sign up to set email alerts
|

A latent profile analysis of age of onset in pathological skin picking

Abstract: Findings suggest the presence of two distinct PSP age of onset groups: (1) an early onset group with average onset in adolescence, clinical characteristics suggestive of greater picking-related burden and familiality, and a profile more representative of the general PSP population; and (2) a late onset group with average onset in middle adulthood, increased co-occurring affective and trauma conditions, and initial onset associated with or following other mental health and physical problems. Future replication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 38 publications
2
19
1
Order By: Relevance
“…The average age at initial diagnosis was 7.93. This is contrary to current studies which have reported ages of 10–13 years at initial TTM diagnosis [5]. Our conflicting finding could be due to the fact that parents/guardians were seeking care at a children’s hospital rather than a general practice or hospital.…”
Section: Discussion/conclusioncontrasting
confidence: 88%
See 2 more Smart Citations
“…The average age at initial diagnosis was 7.93. This is contrary to current studies which have reported ages of 10–13 years at initial TTM diagnosis [5]. Our conflicting finding could be due to the fact that parents/guardians were seeking care at a children’s hospital rather than a general practice or hospital.…”
Section: Discussion/conclusioncontrasting
confidence: 88%
“…In this study, we present data on the clinical and epidemiologic features of TTM in a sample of children at an urban tertiary care center. Most subjects in our cohort were females (65%), keeping with the existing literature [5, 6]. The average age at initial diagnosis was 7.93.…”
Section: Discussion/conclusionsupporting
confidence: 76%
See 1 more Smart Citation
“…While large epidemiological studies are lacking, it is estimated that approximately 1–5% of the general population are affected by SPD (Hayes, Storch, & Berlanga, 2009; Keuthen, Koran, Aboujaoude, Large, & Serpe, 2010). Although SPD symptoms may present across the lifespan, the condition typically emerges in adolescence (Odlaug & Grant, 2008; Ricketts et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Infliction of this behavior using fingernails and fingers was implicated in most of these cases, while others have reported the use of tweezers, pins, tissues, and various other instruments [ 3 ]. The prevalent mean age of onset of SPD in individuals is reported to be approximately 13.6 years [ 4 , 5 , 6 ], with a mean duration of 12.7 years (ranging between three years and 40 years), featuring waxing and waning skin picking episodes throughout the individual’s lifetime [ 5 ]. This is suggestive of SPD possessing a chronic and recurrent nature.…”
Section: Introductionmentioning
confidence: 99%